2018
DOI: 10.1371/journal.pone.0205569
|View full text |Cite
|
Sign up to set email alerts
|

Weak power frequency magnetic fields induce microtubule cytoskeleton reorganization depending on the epidermal growth factor receptor and the calcium related signaling

Abstract: We have shown previously that a weak 50 Hz magnetic field (MF) invoked the actin-cytoskeleton, and provoked cell migration at the cell level, probably through activating the epidermal growth factor receptor (EGFR) related motility pathways. However, whether the MF also affects the microtubule (MT)-cytoskeleton is still unknown. In this article, we continuously investigate the effects of 0.4 mT, 50 Hz MF on the MT, and try to understand if the MT effects are also associated with the EGFR pathway as the actin-cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
1
15
0
1
Order By: Relevance
“…Uniform dispersion in the scaffold may show more contact surface area, thus providing more attachment sites for cell attachment [59]. However, the Fe3O4 nanoparticles are In addition, the magnetic field can also activate various signal pathways of the cell, and collaboratively mediate the signal communication between them, such as the classic mitogen-activated protein kinase [55][56][57] and BMP signal pathway [17,58], thereby promoting the expression of growth factors, improving the activity of runt-related transcription factor 2 and ALP, accelerating the growth and differentiation of osteoblasts, and promoting bone repair finally. Of course, the micro magnetic force generated in the microenvironment of the magnetic scaffold can provide continuous dynamic mechanical stimulation to MG63 cells, which can also improve the cells adhere and migrate.…”
Section: Cell Responsesmentioning
confidence: 99%
“…Uniform dispersion in the scaffold may show more contact surface area, thus providing more attachment sites for cell attachment [59]. However, the Fe3O4 nanoparticles are In addition, the magnetic field can also activate various signal pathways of the cell, and collaboratively mediate the signal communication between them, such as the classic mitogen-activated protein kinase [55][56][57] and BMP signal pathway [17,58], thereby promoting the expression of growth factors, improving the activity of runt-related transcription factor 2 and ALP, accelerating the growth and differentiation of osteoblasts, and promoting bone repair finally. Of course, the micro magnetic force generated in the microenvironment of the magnetic scaffold can provide continuous dynamic mechanical stimulation to MG63 cells, which can also improve the cells adhere and migrate.…”
Section: Cell Responsesmentioning
confidence: 99%
“…Wang et al show that exposure to HMF caused tubulin assembly disorder 38 . Moreover, Wu et al observe that low-frequency sub-millitesla MF modulates the density of MTs in cells 39 . All these observations establish the magnetosensitivity of MTs for wide ranges of MF strengths.…”
Section: Introductionmentioning
confidence: 99%
“…In the following, we review the experimental results for the effects of applied magnetic field 38,39 on the density of MTs. We then describe the quantum spin dynamics of our radical pair model by a simple kinetic model for the MT dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also showed that EMR may cause marked changes in the shape and arrangement of microvilli of the hepatocytes. The changes observed in our experiment could be a consequence of a disturbance of the cytoskeleton, especially actin filaments or changes in the intracellular Ca 2+ concentration (Wu et al 2018).…”
Section: Discussionmentioning
confidence: 75%
“…EMR affects various processes that take place in the cells, such as synthesis of proteins and DNA transcription (Del Re et al 2019), transfer of ions through the cytoplasmic membrane and their subsequent accumulation in the cells (Lange 2000;Sun et al 2016), as well as changes in cytoskeleton organisation (Glade and Tabony 2005;Wu et al 2018).…”
Section: Discussionmentioning
confidence: 99%